(3OQI GdZhGU aj ChgGe GdNhGUs - (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj , J (B516 (3g` s
(3ChdgG (B:s
(3bGd GdTjN CeG HYO MeO Gddg GdPi Ye YHGOg HhXGFa GdYhGQa aEfi QCjJ cKjQkG ef JSfehG CSfeI GdQJH bO VGghG GdYGeI ai HYV eG jaQW ef cdGege aCdaJ gPG GdcJGH JHUQI def JHUQ hSejJg OQI GdZhGU ai ChgGe GdNhGU s
(3BNQgG (B:s
(3aef ChgGege GdaGVMI Cfge jbhdhf bOe SGFQ GdLGL hdgPg GdYdg GNJjGQ HYV GdabgGA Cf jJdi ai JMjGJ GdUdGI hGdSdGe GdChd efcQkG hGdKGfi eYQakG bGd GdTjN agPg GdChgGe ai GdgLGA CKHJgG Yf GdYHGH hGdJbWJgG ef cJH LeGYI ef GdCYjGf hef s
(3GdNW eged GdfbW CMjGfkGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B108s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
Keywords: (3GddZIs